How virtualisation helps smart phones in cloud computing: A survey (International Journal of Engineering and Computer Science, 2014)
The limited capability and energy constraint of smart phones leads to the usage of cloud computing.   Features provided by the cloud aims to augment Smartphone capabilities by providing vast pool of computation power and unlimited storage space. However they are still constrained by limited computing, memory utilization and battery capacity. These limitations can be minimized in smart phones with the help of computation of f loading: sending heavy computation to resourceful servers and receiving the outcome from these servers. Offloading is the latest trend in mobile computing.  In this survey paper we present how offloading can helps to increase the performance of smart phones by providing an overview of techniques, systems, and research areas for offloading computation. We will also describe scope for future research